CHI 98 Conference Summary on Human Factors in Computing Systems 1998
DOI: 10.1145/286498.286784
|View full text |Cite
|
Sign up to set email alerts
|

Designing visualization tools for learning

Abstract: Computer visualizations can be a powerful tool for teaching students about science. But educational visualizations need to be designed with students in mind so that the interface is not only easy to use, but also helps students understand the science that is being visualized. This study looks at the design of visualization tools for middle school students learning thermodynamics. Educational research suggested that a dot-density representation of temperature would help students understanding. Assessments of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…• Provide explicit support for learners to interpret the meaning of visual representations (Foley, 1998;Gordin, Edelson, & Pea, 1996);…”
Section: Direct Learner Attention To Key Variables and Visual Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…• Provide explicit support for learners to interpret the meaning of visual representations (Foley, 1998;Gordin, Edelson, & Pea, 1996);…”
Section: Direct Learner Attention To Key Variables and Visual Cuesmentioning
confidence: 99%
“…For instance an object's density could be represented by superimposing a series of either widely spread or tightly packed dots on the object, rather than displaying numerical representations. Foley (1998) successfully used a "dot density" technique to represent the process of heat flow by increasing or decreasing the density of dots around an object that was cooling. Representing information metaphorically may help give learners a context for reasoning with data and make complex representations more accessible (Tufte, 1983).…”
Section: Provide Explicit Support For Learners To Interpret the Meanimentioning
confidence: 99%
“…Tasker and Dalton (2008) suggest that animations of chemistry should be designed carefully to balance the demands of scientific accuracy, technical constraints, and clarity of communication. Different approaches for designing computer visualizations have been suggested by various researchers (Steinberg, 1984;Soloway et al, 1994;Foley, 1998;Tversky et al, 2006;Kali and Linn, 2008;Mayer, 2009).…”
Section: Designing Visualizationsmentioning
confidence: 99%
“…Some researchers have suggested that the focus of designing visualizations should be the learners (Soloway et al, 1994;Foley, 1998). Foley (1998) claims that educational visualizations should be designed 'with the students in mind'; the interface should be easy to interact with and the visualization should help students to visualize the scientific content. Soloway et al (1994) also emphasize the importance of moving from 'usercentered' to 'learner-centered' design for developing richer and deeper understanding of the content.…”
Section: Designing Visualizationsmentioning
confidence: 99%
“…Several researchers have investigated the use of computers, specifically simulation and visualization technology in experiments. Foley had shown that computer simulation and visualization can be very effective in enhancing student learning if the interface is based on education research [2].…”
Section: Introductionmentioning
confidence: 99%